Increasing Basic Mathematics Ability Using Manipulative Media - Susilawati, Eneng Sri; Syahrial, Zulfiati; Soekardjo, Moch (International Journal of Psychosocial Rehabilitation, 2020)
This research was aimed at increasing basic mathematics ability in numerical operations aspects of B level students at Prosperous I Kindergarten in Panggarangan using manipulative media. It was carried out in April to May 2019. The action research of Kemmis and Taggart was used as the method of the research. It applied two cycles with 12 meetings. The cycles consist of planning, acting, observing, and reflecting. The subject of the research were 13 kindergarten level B students of Prosperous I Panggarangan. The data obtained were assessment results of pre-cycle, cycle I and cycle II, field notes, interviews, and documentation. Emills standard was used to analyze the data percentage, that the average increase of basic mathematics ability in numeral operation aspects reached 71%. The result of the research shows that there was an increase in basic mathematics ability using manipulative media. It was proven by the increase of students' average assessment results. In cycle I the students' average score was 27,7, in cycle II it was 32.2. It means that there was an increase of 4,5 in the average score, from 76.9% in cycle I to 89.5% in cycle II. The implication of this study indicated that the use of manipulative media to teach basic mathematics in numerical operations brought about good results. In the learning process, the students become more active and creative. They found it easier to learn some mathematics concepts. In teaching mathematics concepts, manipulative media helped ease the teacher in explaining the concepts.